The prediction of time-dependent deformation of normal strength concrete in tropical climate - Omar, Roslina (2009)
Realistic prediction of concrete creep and shrinkage is crucial for durability and long-term serviceability of concrete structure and also stability and safety against collapse. Creep and shrinkage may increase the deflection and curvature and may cause cracking and loss of pre-stressing force in prestressed concrete. Creep and shrinkage are known to be influenced by many factors such as the type of cement, water-cement ratio, curing condition, relative humidity, temperature, age and size of the member. Until recently, data is scarcely available on the time-dependent deformations of concrete in the tropical climate compared to those in the temperate climate where more substantial studies have been performed. The current practice of evaluating time-dependent and elastic deformations in concrete structures in Malaysia is to refer to British Standard (BS 8110) or other international standards. In the near future, reference will be made to Eurocode 2 (EC 2) that is foreseen to supersede BS 8110. Therefore, this research is carried out to improve the creep and shrinkage prediction model of Malaysian concrete. The strengths of concrete investigated are in the range of 20 to 40 N/mm2. The testing for creep and shrinkage were carried out according to standard method provided in ASTM C512-87 and ASTM C157-91. From the comparison of experimental data collected to the existing models of EC 2, American Standard (ACI 209), CEB-FIP 1990 and Australian Standard (AS 3600), EC 2 best predicts the results followed by AS3600. With the aim of getting an accurate prediction of creep and shrinkage for concrete in tropical climate, the EC 2 models were selected and modified. The modification factors in the range of 0.85 – 1.69 for creep and 0.65 - 0.79 for shrinkage, depending on the concrete strength, are introduced based on the experimental results. These factors are proposed to be applied to EC 2 model in order to give better prediction of time-dependent deformation of normal strength concrete in tropical climate.